2012
DOI: 10.1016/j.cmet.2011.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Autophagy in Pro-opiomelanocortin Neurons Perturbs Axon Growth and Causes Metabolic Dysregulation

Abstract: Summary The hypothalamic melanocortin system, which includes neurons that produce proopiomelanocortin (POMC)-derived peptides, is a major negative regulator of energy balance. POMC neurons begin to acquire their unique properties during neonatal life. The formation of functional neural systems requires massive cytoplasmic remodeling that may involve autophagy, an important intracellular mechanism for the degradation of damaged proteins and organelles. Here we investigated the functional and structural effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
151
3
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(172 citation statements)
references
References 41 publications
11
151
3
7
Order By: Relevance
“…Multiple studies have demonstrated that Atg7 deletion in POMC neurons causes increased body weight owing to hyperphagia [87][88][89] . However, more recent research argues against a general role for POMC neuron-specific autophagy in the control of energy homeostasis.…”
Section: Danon Diseasementioning
confidence: 99%
“…Multiple studies have demonstrated that Atg7 deletion in POMC neurons causes increased body weight owing to hyperphagia [87][88][89] . However, more recent research argues against a general role for POMC neuron-specific autophagy in the control of energy homeostasis.…”
Section: Danon Diseasementioning
confidence: 99%
“…Autophagy knockout in adipose tissue also leads to protection from diet-induced obesity and insulin resistance together with impaired adipocyte differentiation 7,9 . Autophagy deficiency in hypothalamic proopiomelanocortin neurons leads to obesity and glucose intolerance [47][48][49] . In addition to the location of autophagy deficiency, severity of autophagy deficiency could also be important.…”
Section: Discussionmentioning
confidence: 99%
“…1). [7][8][9] These studies used a conditional cre-loxP approach to specifically delete Atg7 from POMC neurons. PomcCre; Atg7 loxploxp mice display higher body weights, hyperphagia and impaired glucose tolerance.…”
mentioning
confidence: 99%
“…1). 7 PomcCre; Atg7 loxPloxP mice exhibit a reduced density of POMC-containing projections to each of their target nuclei, including the paraventricular nucleus of the hypothalamus, as early as postnatal day 14. These abnormalities in POMC neural projections persist throughout adult life and appear to be the result of diminished capacity of POMC neurons to extend axons.…”
mentioning
confidence: 99%
See 1 more Smart Citation